Arthroscopic Treatment for Femoroacetabular Impingement with Extraspinal Diffuse Idiopathic Skeletal Hyperostosis - Hwang, Jung-Mo; Hwang, Deuk-Soo; Kang, Chan; Lee, Woo-Yong; Lee, Gi-Soo; Lee, Jeong-Kil; Kim, Yun-Ki (Clinics in orthopedic surgery, 2019)
Patients with extraspinal diffuse idiopathic skeletal hyperostosis (DISH) involving the hip joint have symptoms like femoroacetabular impingement (FAI). To date, no reported study has determined the clinical outcomes of arthroscopic treatment in extraspinal DISH involving the hip joint. A total of 421 hips with FAI that underwent arthroscopic treatment were reviewed retrospectively. We determined the extraspinal involvement of DISH with three-dimensional computed tomography (3D-CT) and simple radiography of the pelvis and hip joint. Clinical outcomes were evaluated at a minimum of 2 years postoperatively. The visual analog scale score (VAS), modified Harris hip score (MHHS), and hip outcome score-activity of daily living scale (HOS-ADL) were used, and hip range of motion (ROM) was evaluated pre- and postoperatively and at the time of the final follow-up. Among the 421 hips (372 patients) with FAI that underwent arthroscopic treatment, 17 hips (12 patients, 4.04%) had extraspinal DISH on the hip joints. The mean age of the patients was 51.5 years. The 3D-CT scans and simple radiographs showed extraspinal DISH on multiple points around the pelvis and hip joint. Nine of the 17 hips (seven of 12 patients) had spinal DISH. At the final follow-up, VAS, MHHS, and HOS-ADL improved significantly from 6.5, 65.3, and 66.6, respectively, to 1.2, 87.8, and 89.5, respectively, and hip flexion and internal rotation improved significantly from 97.7° and 7.9°, respectively, to 117.1° and 18.2°, respectively. This study has demonstrated that extraspinal DISH involving the hip joint could lead to FAI, and arthroscopic treatment could result in relief of symptoms, including pain and ROM limitation, in extraspinal DISH patients.